Repetitions in Gesture A Cognitive-Linguistic and Usage-Based Perspective - Bressem, Jana (Applications of cognitive linguistics ;, 2021)
Repetitive sequences play a major role as a pattern-building device and are a basic syntagmatic linguistic means on all language levels in spoken and signed languages. Little attention has been paid to investigating them in multimodal language use. Do gestures exhibit different types of repetitive sequences? Do they build complex units based on these types and if so, how is the pattern building to be described? How is the interrelation of gestural and spoken units in such complex units? Is it possible to identify repetitive patterns that are comparable to spoken and signed languages and/or patterns specific to the gestural modality? Based on a corpus-analysis of multimodal usage-events, 7 chapters explore gestural repetitions with regard to their structure, semantic and syntactic relevance for multimodal utterances, and cognitive saliency. Fine-grained cognitive-linguistic analyses of multimodal usage events reveal that gestural repetitions are not only a basic principle of building patterns in spoken and signed languages, but also in gestures. By addressing questions of mediality and multimodality of language-in-use, the book contributes to the investigation of repetition as a fundamental means of sign and meaning construction (crosscutting modalities) and enhances the understanding of the multimodal character of language in use.